PENGEMBANGAN BIBIT PORANG DARI BEBERAPA SUMBER DENGAN BERBAGAI MEDIA TUMBUH MELALUI TEKNIK POTTING MIX PADA TANAH ENTISOL - Ardianti, Risma; Suwardji, Suwardji; AB, Baharuddin (Department of Soil Science, Faculty of Agriculture, University of Mataram, 2024)
Porang plants (Amorphophallus muelleri Blume) are herbaceous plants that are commonly found growing wild in forested areas, under bamboo clumps, along riverbanks, on mountain slopes, amidst dense and humid vegetation. Porang propagation from corms and cormels requires a considerable amount of time, around 7-9 months. Therefore, there is a need for the development of porang seedlings through easy vegetative propagation methods that can be implemented at the farmer level. This research utilized Entisol soil originating from Andalan Village, Bayan Subdistrict, North Lombok Regency. The research was conducted using an experimental method. The treatments were arranged using a Completely Randomized Design (CRD) involving 4 seed sources (porang cormels/bulbils, split corms, porang leaves, and porang stems) with 3 treatments, namely no treatment, biochar, liquid organic fertilizer, PGPR, and Trubus plant growth regulator. The analysis of variance results showed that the application of various growing media (biochar, liquid organic fertilizer, and PGPR) influenced changes in soil properties and the growth of porang seedlings. The growth of porang seedlings was influenced in the split corm and cormel techniques. Further tests indicated that the cormel technique, specifically in terms of plant height and stem diameter, was affected by the addition of organic materials compared to the absence of organic material application